Melodrama in Contemporary Film and Television
XVI, 262 p.
Keywords: Melodrama in Contemporary Film and Television debates the ways in which melodrama expresses and gives meaning to: trauma and pathos; memory and historical re-visioning; home and borders; gendered and queer relations; the family and psychic identities; the national and emerging public cultures; and morality and ethics.